Exploring the Implementation of Entrepreneurship Education in the UAE’s Higher Education Institutions: Perspectives of Faculty Members, Academic Leaders and Policymakers - Thani Al Dhaheri, Reem (2020)
Supporting entrepreneurship has recently become one of the most prominent national policies in the UAE in order to promote economic development. Consequently, entrepreneurship education is gaining more and more attention from the government, and higher education institutions are being called upon to play a vital role in promoting entrepreneurship. The purpose of this study is to examine the views of entrepreneurship faculty members, higher education institutions’ academic leaders and government policy makers about the implementation of entrepreneurship education in higher education institutions in the UAE. The theoretical framework on which the study was based includes three components: human capital theory, the entrepreneurship education teaching model and experiential learning. The main data collection methods used for this qualitative study were semi-structured interviews and document analysis. Interviews were held with policy makers, higher education institutions’ entrepreneurship faculty and academic leaders, as well as analysis of documents from the UAE government and participating higher education institutions, including the Stanford University programme in the US that trained UAE faculty members in entrepreneurship. A qualitative thematic data analysis approach was conducted to answer the research questions. The findings of the study support the research in suggesting that entrepreneurship needs to be infused across the curricula of all undergraduate programmes in the UAE as a key competency. The findings also highlight the importance of creating entrepreneurship courses and programmes that are suitable for Emirati students through contexualisation and localisation of content and teaching methods. Based on the findings, the study recommends that the Ministry of Education in the UAE lead the development of comprehensive national entrepreneurship education policies, as well as oversee the development of similar policies within higher education institutions. The study also recommends creating an environment in higher education institutions that is more conducive for entrepreneurship, including by offering various on-campus support services and by developing productive partnerships with industry and the community.